Poplar PsnICE1 enhances cold tolerance by binding to different cis-acting elements to improve reactive oxygen species-scavenging capability. (29th June 2021) - Wang, Yan-Min; Zhang, Yi-Ming; Zhang, Xin; Zhao, Xin; Zhang, Yu; Wang, Chao; Wang, Yu-Cheng; Wang, Liu-Qiang
Abstract: Low temperature is a major stress that severely affects plant growth and development. Inducer of CBF expression 1 (ICE1) plays a key role in plant cold tolerance by regulating the expression of cold stress-responsive genes. In the present study, we characterized the function and underlying regulatory mechanism of PsnICE1 from Xiaohei poplar ( Populus simonii × Populus nigra ). PsnICE1 was significantly induced in response to cold stress in the roots, stems and leaves. PsnICE1 proteins were found to localize to the nucleus and exert transactivation activity via their N-terminal transactivation domain. Compared with non-transgenic poplar, transgenic poplar overexpressing PsnICE1 showed substantially enhanced tolerance to cold stress, with higher survival rates and antioxidant enzyme activity levels and reduced reactive oxygen species (ROS) accumulation. In contrast, plants with RNA inhibition-mediated silencing of PsnICE1 showed the opposite phenotype. PsnICE1 can bind to H-box element and abscisic acid-responsive element (ABRE), and more importantly, it mainly binds to IBS1 (a newly discovered cis-acting element) and E-box elements to regulate stress-related genes involved in ROS scavenging. Overall, these results indicated that PsnICE1 functions as a positive regulator of cold tolerance and serves as a potential candidate gene for plant cold tolerance improvement via molecular breeding.